Higher Expression Levels of Aquaporin Family of Proteins in the Kidneys of Arid-Desert Living Lepus yarkandensis - Zhang, Jianping; Li, Shuwei; Deng, Fang; Baikeli, Buheliqihan; Huang, Shuguang; Wang, Binyu; Liu, Guoquan (Frontiers in Physiology, 2019)
Lepus yarkandensis specifically lives in arid climate with rare precipitation of Tarim Basin in western China. Aquaporins (AQPs) are a family of channel proteins that facilitate water transportation across cell membranes. Kidney AQPs play vital roles in renal tubule water permeability and maintenance of body water homeostasis. This study aimed to investigate whether kidney AQPs exhibit higher expression in arid-desert living animals. Immunohistochemistry results revealed localization of AQP1 to the capillary endothelial cells in glomerulus and epithelial cells in proximal tubule and descending thin limbs, AQP2 to the apical plasma membrane of principal cells in the cortical collecting duct (CCD), outer medullary collecting duct (OMCD), and IMCD cells in the initial inner medullary collecting duct (IMCD1) and middle IMCD (IMCD2), and AQP3 and AQP4 to the basolateral plasma membrane of principal cells and IMCD cells in CCD, OMCD, IMCD1 and IMCD2 in L. yarkandensis kidneys. Quantitative real-time PCR analysis showed higher mRNA levels of AQP1, AQP2, AQP3 and AQP4 in L. yarkandensis kidneys compared with Oryctolagus cuniculus. Similar results were obtained by western blotting. Our results suggested that higher expression levels of AQP1, AQP2, AQP3 and AQP4 in L. yarkandensis kidneys favored for drawing more water from the tubular fluid.